INFLUENCE OF HOUSING RIBBING MODIFICATION ON FREQUENCIES AND SHAPES OF VIBRATIONS - Piotr FOLĘGA; Grzegorz WOJNAR; Piotr CZECH (Scientific Journal of Silesian University of Technology. Series Transport)
In article an experimental and theoretical modal analysis of selected structural solutions of housings gear was carried out. Results of the examinations enabled to determine a rate of FEM modal parameters conformity with parameters of actual objects by determination of MAC ratio value. Basing on obtained results of the experimental modal analysis, the numerical models of housings were fine tuned. The obtained conformity of the results of experimental and theoretical modal analysis of examined housings’ solutions enabled to ascertain the correctness of prepared FEM models. The executed modal analysis of various housing versions enabled to estimate influence of made ribbing modifications on form and frequency of its own vibrations.